The Accuracy of High Alert Medication Storage in the Pharmacy Installation of RSUD Dr. Soegiri Lamongan: Storage of High Alert Medication at the Pharmacy Installation of RSUD Dr. Soegiri Lamongan; Accuracy of Drug Storage High Alert Medication - Rahmadinah, Hifar (Berkala Ilmiah Mahasiswa Farmasi Indonesia, 2024)
Rahmadinah, H. 2022. Accuracy of Storage of High Alert Medication in the Pharmacy Installation of RSUD Dr. Soegiri Lamongan 2022. Thesis. Pharmacy Study Program, Faculty of Medicine and Health Sciences, Maulana Malik Ibrahim State Islamic University, Malang. Supervisor I : apt. Hajar Sugihantoro, S.Farm., M.P.H.; Supervisor II : apt. Ah. Syahrir, M. Farm. High Alert Medication (HAM) is a group of drugs that need to be watched out for in their use because they can lead to high use of unwanted drugs (Medication Error). The highalert medication group is divided into LASA (Look A Like Sound A Like) drugs, highly concentrated electrolytes, and cytostatics (cancer drugs). The purpose of this study was to determine the profile and accuracy of storage of LASA (Look A Like Sound A like) drugs and high-concentrate electrolytes based on the issued SOPs. This research includes descriptive research by observing, classifying, recording, and analyzing with SOP guidelines. The sample of this study used LASA (Look A Like Sound A Like) drugs and highly concentrated electrolytes. Location The research was conducted at the pharmacy installation of RSUD Dr. Soegiri Lamongan in 2022. The results show that the storage profile of LASA (Look Alike Sound A Like) and high concentrate electrolytes uses a storage method based on the storage method based on the form and type of pharmaceutical preparations, FIFO, FEFO, and alphabetically. The storage accuracy of LASA drugs (Look Alike Sound A Like) for indicators of separated LASA drugs with their equivalents is 97.72% and LASA drugs labeled "LASA" with a yellow base is 90.9%. Accuracy of high-concentrated electrolyte drug storage for indicators Highconcentrated electrolyte medicine is labeled “High Alert” at 100% and high-concentrated electrolyte medicine is labeled “Concentrated Electrolyte” with a yellow base color of 100%. Based on these results, it can be concluded that the LASA (Look Alike Sound A Like) storage has not met the accuracy based on the issued SOP. Keywords : LASA (Look A Like Sound A Like), high concentrate electrolyte, Medication Error